Intertrochanteric Fracture of the Ankylosed Hip Joint Treated by a Gamma Nail: A Case Report. (1st August 2012) - Ishimaru, Daichi; Nozawa, Satoshi; Maeda, Masato; Shimizu, Katsuji
Abstract : We herein report a rare case of an intertrochanteric fracture complicated with an ankylosed hip joint in a 76-year-old man. Generally, operative treatment is performed for elderly people with intertrochanteric fractures to prevent general complications, maintain mobility, and release pain. However, intertrochanteric fractures of ankylosed hip joints are rare, and the optimal surgery for this condition is unknown. In addition, surgical fracture repair is challenging because unusual instability of the fracture site is suspected owing to the long lever arm of the lower extremity. Nevertheless, we successfully treated this rare fracture using a gamma nail, which may be a useful implant with which to treat this type of fracture if the status of the arthrodesed hip joint allows.